Europe et identité nationale française : d’un référendum à l’autre, 1992-2005 - Dubé-Senécal, Vincent (Université de Montréal, 2014)
The European project, through each of its milestones, outlines a new type of entity on the international scene, one which is a stranger to the nation state without being its better. From the intensification of European integration emerged a questioning on the nature of the interactions between national and European identity. In this respect, France represents a very interesting field of study as the country organised two referendums on European integration, one in 1992 and the other in 2005. The main goal of this research is to reveal the way in which the construction of a national discourse within the French public opinion is influenced by the deepening of European integration. The analysis covers both debate periods before the 1992 and 2005 referendums dealing with the ratification of the Maastricht Treaty on the Euro and the Treaty establishing a Constitution for Europe. This work is based on a press analysis covering both periods of debate. In order to study the evolution of the French perception of their national identity with the least political bias possible, this thesis relies on documentary resources comprising editorials and letters to the editor of four newspapers: Le Monde, Le Figaro, L’Humanité and Libération. The comparison of the identity discourses of 1992 and 2005 reveals that the relation of identification between France and Europe has drastically changed during this period. It went from a relation founded on alterity to a relation founded on shared values. In 1992, the French use the European idea as an identity referent around which they reaffirm the “frenchness” of their shared values. In 2005, the French national identity is not in question anymore. From now on, the debate turns around the values the French hope to see at the root of the European identity to which they are called to adhere. These values are henceforth drawn from the personal identity of each Frenchman rather than from an encompassing concept of the French national identity.
Keywords: Constitution européenne; European Constitution; France; History - European / Histoire - Européenne (UMI : 0335); Identité nationale; Maastricht; National identity; Referendums; Référendums